Lightweight single image super-resolution with dense connection distillation network - Li, Yanchun; Cao, Jianglian; Li, Zhetao; Oh, Sangyoon; Komuro, Nobuyoshi (ACM Transactions on Multimedia Computing, Communications and Applications, 2021)
Single image super-resolution attempts to reconstruct a high-resolution (HR) image from its corresponding low-resolution (LR) image, which has been a research hotspot in computer vision and image processing for decades. To improve the accuracy of super-resolution images, many works adopt very deep networks to model the translation from LR to HR, resulting in memory and computation consumption. In this article, we design a lightweight dense connection distillation network by combining the feature fusion units and dense connection distillation blocks (DCDB) that include selective cascading and dense distillation components. The dense connections are used between and within the distillation block, which can provide rich information for image reconstruction by fusing shallow and deep features. In each DCDB, the dense distillation module concatenates the remaining feature maps of all previous layers to extract useful information, the selected features are then assessed by the proposed layer contrast-aware channel attention mechanism, and finally the cascade module aggregates the features. The distillation mechanism helps to reduce training parameters and improve training efficiency, and the layer contrast-aware channel attention further improves the performance of model. The quality and quantity experimental results on several benchmark datasets show the proposed method performs better tradeoff in term of accuracy and efficiency.
Keywords: Attention mechanisms; Benchmark datasets; Feature fusion; High resolution image; Low resolution images; Super resolution; Training efficiency; Training parameters; attention mechanism; Dense connection; single image super-resolution